La odisea de la especie: el porvenir lejano de la humanidad - Rovaletti, María Lucrecia (Acta Bioethica, 2005)
The notion of "technical transcendency" or "operatory" is raised starting from man's definition as a "praxis being". Since technoscience establishes that limits are settled to be transgressed, it is compared with the concept of "utopia" as an "transcendental operator" (S. Breton). This leads us to think about a new "evolution" not due to natural changes, but to human technoscientific power. Thus, we have two alternatives: confrontations and breaches, or a fair and reasoned debate of each situation.